Blood of my blood ebook - Lyga, Barry (I Hunt Killers, 2014)
The final book in this thrilling, terrifying series by New York Times bestselling author Barry Lyga is perfect for fans of Dexter . Jazz Dent has been shot and left to die in New York City. His girlfriend Connie is in the clutches of Jazz's serial killer father, Billy. And his best friend Howie is bleeding to death on the floor of Jazz's own home in tiny Lobo's Nod. Somehow, these three must rise above the horrors their lives have become and find a way to come together in pursuit of Billy. But then Jazz crosses a line he's never crossed before, and soon the entire country is wondering: "Like father, like son?" Who is the true monster? The chase is on, and beyond Billy there lurks something much, much worse. Prepare to meet...the Crow King.